-5+(-15d+1)=2(7d-16)-d

Simple and best practice solution for -5+(-15d+1)=2(7d-16)-d equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5+(-15d+1)=2(7d-16)-d equation:


Simplifying
-5 + (-15d + 1) = 2(7d + -16) + -1d

Reorder the terms:
-5 + (1 + -15d) = 2(7d + -16) + -1d

Remove parenthesis around (1 + -15d)
-5 + 1 + -15d = 2(7d + -16) + -1d

Combine like terms: -5 + 1 = -4
-4 + -15d = 2(7d + -16) + -1d

Reorder the terms:
-4 + -15d = 2(-16 + 7d) + -1d
-4 + -15d = (-16 * 2 + 7d * 2) + -1d
-4 + -15d = (-32 + 14d) + -1d

Combine like terms: 14d + -1d = 13d
-4 + -15d = -32 + 13d

Solving
-4 + -15d = -32 + 13d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-13d' to each side of the equation.
-4 + -15d + -13d = -32 + 13d + -13d

Combine like terms: -15d + -13d = -28d
-4 + -28d = -32 + 13d + -13d

Combine like terms: 13d + -13d = 0
-4 + -28d = -32 + 0
-4 + -28d = -32

Add '4' to each side of the equation.
-4 + 4 + -28d = -32 + 4

Combine like terms: -4 + 4 = 0
0 + -28d = -32 + 4
-28d = -32 + 4

Combine like terms: -32 + 4 = -28
-28d = -28

Divide each side by '-28'.
d = 1

Simplifying
d = 1

See similar equations:

| 21x-5-16x+2=17x-9-12x+15 | | 6x-16=-96 | | 3(c+5)= | | 4r=-28 | | 23b-19b= | | (10x+3)=(15x-7) | | 15x+14y+27x=0 | | 14x-7=12x+3 | | 9y+11y= | | y=100 | | (4t+16)=(5t-21) | | a-3.5=19.5 | | x=4-2x | | 2a-21.2=a+1.8 | | 9x-8+4x=13x-8 | | 3(2x+5)=2(4x-5)3x | | X(x-15)=35 | | 4n+5(7n-3)=9(n-5) | | (6a-4)=(4a+36) | | 6x=7x-9 | | 4x(x+5)-11=4x^2+17x+1 | | 2.3x+6=-4.3x+9 | | 30(x-5)=30 | | 5w+3w=24 | | 5r^2+12z+4=0 | | 2(3h+11)=6h+4 | | 3(2x+5)=-7(3-2x) | | (3e-32)+(e+16)=180 | | 20y+2(5-15y)=0 | | 18(m+6)=15m-6 | | 10x+12y=166 | | 10x-2(x-3)=8(x+1)+9 |

Equations solver categories